2014
DOI: 10.18388/abp.2014_1877
|View full text |Cite
|
Sign up to set email alerts
|

Plant expression systems for production of hemagglutinin as a vaccine against influenza virus.

Abstract: Many examples of a successful application of plant-based expression systems for production of biologically active recombinant proteins exist in the literature. These systems can function as inexpensive platforms for the large scale production of recombinant pharmaceuticals or subunit vaccines. Hemagglutinin (HA) is a major surface antigen of the influenza virus, thus it is in the centre of interests of various subunit vaccine engineering programs. Large scale production of recombinant HA in traditional express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Many studies have been reported on the development of plant‐based influenza subunit vaccines (reviewed in Chichester et al ., ; D'Aoust et al ., ; López‐Macías, ; Redkiewicz et al ., ; Yusibov et al ., ). In regard to structure, three types of plant‐produced influenza subunit vaccine candidates have been produced: monomeric HA, trimeric HA and HA‐based enveloped VLPs.…”
Section: Advances In the Development Of Plant‐based Subunit Vaccinesmentioning
confidence: 98%
“…Many studies have been reported on the development of plant‐based influenza subunit vaccines (reviewed in Chichester et al ., ; D'Aoust et al ., ; López‐Macías, ; Redkiewicz et al ., ; Yusibov et al ., ). In regard to structure, three types of plant‐produced influenza subunit vaccine candidates have been produced: monomeric HA, trimeric HA and HA‐based enveloped VLPs.…”
Section: Advances In the Development Of Plant‐based Subunit Vaccinesmentioning
confidence: 98%
“…In this clinical study, 18-49 years old subjects were intramuscularly administered H1-VLPs at 5-, 13-, and 28-μg H1 HA-VLPs. The clinical results were found to be safe and well tolerated at all dose levels and even 5-µg dose of VLPs induced greater than 1:40 HAI titers in 83% of the subjects in this lowvaccine dose group [43] (Table 4). Two randomized Phase II clinical trials in 18 to 49 and over 50 years old adults have shown that the 30-µg dose of quadrivalent plant-derived influenza VLP vaccine produced consistent humoral and cellular responses [129].…”
Section: Clinical Studies Of Influenza Vlp Vaccinesmentioning
confidence: 88%
“…In brief, mammalian cells were co-transfected with three different cloned recombinant plasmids such as M1, HA, and NA, respectively, M1 from A/ Puerto Rico/8/1934 strain, NA from A/Thailand/1(KAN-1)/2004 and codon-optimized HA protein from clade 2 H5N1. Plant cells are being used for expression and production of recombinant HA influenza VLP vaccines, which are currently under clinical trials to evaluate the immunogenicity, safety, and efficacy [43] (Tables 1 and 2). Various forms of recombinant HA, including monomers, trimers, virus-like particles or chimeric proteins were obtained by plant-based technology.…”
Section: Production and Immunogenicity Of Influenza Vlp Vaccines Targmentioning
confidence: 99%
See 2 more Smart Citations